Factors Influencing Help Seeking Among Battered Women I Spousal Relationships In Nakuruwest Sub County, Kenya - Wachira, Mary; Ngetich, Kibet; Mwangi, Wokabi (Advances in Social Sciences Research Journal, 2017)
Family stability is the heart to a stable society. Wife battering has been recognized as a hindrance to this stability because it not only negatively affects the women who are its primary victims but also their children who depict the continuity of any society. This paper was motivated by the fact that even though wife battering has for long been recognized as not only a health hazard but also a grave violation of human rights, it continues to be prevalent in many families. Nakuru West Sub-County was purposively selected because though the vice occurs in many families in the area, very few cases are reported in the area thus making it necessary to identify factors influencing help seeking choices among battered women. The study was guided by two theories; Battered Women Syndrome Theory and Survivor Theory. Snowball and purposive sampling methods were used to identify the sample size required. A qualitative research methodology employing an Interview Schedule, Focus Group Discussions and Key Informants Guides was employed as the tools of data collection and data was analyzed using descriptive statistics. Statistical Packages for Social Sciences (SPSS version 17) was used for analysis. The study found that majority (80.0%) of the battered women do not always seek help. The respondents argued that a variety of factors prevent help seeking including concern for children, protecting family, mistrust ,fear, culture, personal believes just to mention but a few. This study recommends social solutions to wife battering because findings conclude that it is a social problem. The study also recommends that policies to curb battering be more stringent in order to deal with the menace thereby empowering women who are key pillars to family welfare and by extension stable society.